New religious travel segment - Siti Atikah, R. *; Tan, Ai Ling *; Trupp, Alexander *; Chong, Daniel Ka Leong *; Vijaya Malar, V. A. * (2021)
The focus of this study is on the emergence of a new religious travel segment: Umrah Do It Yourself (DIY) travelers. The Umrah journey is organised by a specially licenced travel agent who handles all of the necessary arrangements, including flights and trip itineraries. However, a small percentage of travellers choose not to use such agencies and instead make their own arrangements, and the Saudi Arabian government's intention to launch a Tourist e-Visa in September 2019 has provided a window of opportunity to legalise Umrah DIY excursions. The study's objectives are to investigate how travel motivations contribute to the success of Umrah DIY. A hermeneutic phenomenological technique was employed to address the research gap. Participants were recruited via an Umrah DIY Facebook group, where 20 people volunteered and signed consent forms to help with the research process. According to the findings, the most crucial reason to engage on this quest is flexibility. This study aims to fill the gap of "religion" as a travel element, which is seen as an opportunity for suppliers and industry participants to address this segment by gaining a better understanding of their travel motivations as the foundation for developing relevant religious tourism products and services. Religious and spiritual journeys in Islam are classified into three types: Hajj, Umrah, and Ziyara (Hassan et al., 2015; Timothy & Olsen, 2006). While Umrah is part of the journey to Mecca, Muslims are only required to perform the first Umrah. According to Hassan et al. (2015), Umrah can be performed more than once, and it can be repeated dependent on the individual's physical and financial abilities. Hajj and Umrah travel have been mostly organised in a closely controlled manner in - packaged group tours (Haq & Jackson, 2009). According to Hassan et al. (2016), Umrah package travellers are those who buy products (Umrah package travel) from local tour operators and travel agents for religious and spiritual reasons, combining lodging, transportation, itinerary, and meals. The Kingdom of Saudi Arabia issued over four million Umrah visas in 2013 to travellers from 70 countries, and the number of visitors increased year after year until the outbreak of COVID-19 (Muneeza & Mustapha, 2021). Recent trends in Umrah individualism and Do-it-yourself (DIY) travel can be seen (Almuhrzi & Alsawafi, 2017). This is also demonstrated by the Umrah DIY Facebook forum, which has 10,000 members, and current articles about Umrah DIY conducted in Indonesia (Lailatul & Melinda, 2018; Ubaidillah, 2021). Despite the fact that significant proof has already been provided on Umrah travellers' journeys, there is a lack of explanation on Umrah DIY travellers. The only study on Umrah DIY found focused on the feasibility of Umrah backpackers among young Indonesian travellers (Lailatul & Melinda, 2018; Fakhruddin & Ubaidillah, 2021), and Hajj backpackers on the possibilities and obstacles of religious travellers (Kusumaningtyas, 2019). With the Saudi Arabian government's reform of the E-Umrah Visa policy in 2019, there is an increasing trend of international pilgrims travelling to the holy sites to perform their Umrah on their own rather than through travel agencies. Flexibility, information sources, familiarity, travel quality, companion, budget travel, and spirituality are emerging themes that explain why Umrah DIYers choose to organise and handle their most significant lifetime journey on their own. Furthermore, as travellers seek ways to maximise their experiences, this research could aid in the development of DIY Umrah travel choices.